2009
DOI: 10.1128/aem.00507-09
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of O Island 48 to Adherence of Enterohemorrhagic Escherichia coli O157:H7 to Epithelial Cells In Vitro and in Ligated Pig Ileal Loops

Abstract: O island 48 (OI-48) ofThe OI-48 aidA gene deletion had no effect on adherence in vitro or in vivo. Deletion of the iha and ureC genes had no effect on adherence in vitro but significantly reduced the colonization of EHEC O157:H7 in the ligated pig intestine. These data suggest that Te r , Iha, and urease may contribute to EHEC O157:H7 pathogenesis by promoting adherence of the pathogen to the host intestinal epithelium.The genome of enterohemorrhagic Escherichia coli (EHEC) O157:H7 strain EDL933 contains uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 31 publications
(36 reference statements)
0
47
4
Order By: Relevance
“…This region was similar to the urease-tellurite islands found in E. coli O157:H7 strains, EHEC O26:H11 strain 11368, and EHEC O111:H Ϫ strain 11128 (51). Previous studies have identified this island among porcine ETEC O149:K88 strains (39), and portions of this island in E. coli O157:H7 were shown to be involved in colonization to ligated pig intestine (56). Therefore, this island might be important for the colonization of UMNK88 and other K88 strains.…”
Section: Resultsmentioning
confidence: 56%
“…This region was similar to the urease-tellurite islands found in E. coli O157:H7 strains, EHEC O26:H11 strain 11368, and EHEC O111:H Ϫ strain 11128 (51). Previous studies have identified this island among porcine ETEC O149:K88 strains (39), and portions of this island in E. coli O157:H7 were shown to be involved in colonization to ligated pig intestine (56). Therefore, this island might be important for the colonization of UMNK88 and other K88 strains.…”
Section: Resultsmentioning
confidence: 56%
“…Urease has been confirmed as an important virulence factor in several bacterial species, such as Helicobacter pylori, Yersinia enterocolitica, Proteus mirabilis, Brucella species, and Klebsiella pneumoniae (31). Mutation of ureC has led to a reduced adherence of EHEC O157:H7 in ligated pig intestine (12). A recent study by Steyert and Kaper (32) revealed that strains with nonfunctional urease were 2-fold less likely to survive passage through the stomach and had a reduced ability to colonize the mouse intestinal tract compared to urease-positive strains.…”
Section: Figmentioning
confidence: 99%
“…The role of tellurite resistance genes (terZABCDEF) in STEC is still not well understood. Yin et al (12) showed that mutation of the ter cluster in O157:H7 led to fewer adherence to epithelial cells and smaller bacterial clusters compared to wildtype strains. Therefore, ter genes might encode an adhesin or a gene product that promotes the function of adhesion(s).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of the ter operon from uropathogenic E. coli KL53 into non-pathogenic and uropathogenic E. coli (ter-gene free) showed that the presence of the ter loci improved the fitness of bacterial strains by enabling them to survive inside macrophages (Valkova et al 2007). Deletion of the Te R region reduced the ability of the strain to adhere to epithelial cells in vitro and in ligated pig ileal loops (Yin et al 2009). In spite of the rare occurrence of tellurite in nature, the acquisition of the ter operon could offer some selective advantage to pathogens in natural environments, such as the urinary tract of humans, and facilitate colonisation despite immune assault.…”
Section: Discussionmentioning
confidence: 99%